PERAN KEPALA SEKOLAH DALAM MEMBANGUN BUDAYA ORGANISASI DI SMP NEGERI PULAU LEBAR MUSI RAWAS UTARA - Siti Sutarsih (Jurnal Perspektif Pendidikan, 2020)
The purpose of this study was to analyze what efforts were made by school principals in fostering organizational culture and teacher performance in learning. This research is a qualitative research with data collection techniques, through observation, interviews and documentation. This research was carried out in Pulau Lebar State Junior High School. The analysis technique used in this study uses descriptive analytic techniques. The results showed (1) Organizational culture in Pulau Lebar State Junior High School in several school activities, family atmosphere, and role models given by the school principal; (2) The principal's efforts in fostering cultural organizations are carried out in two ways, namely the way the principal is shown with the role and responsibility as a leader, and through self-development activities for students. (3) Principal's techniques for improving teacher performance in high-level learning, private meetings, teacher council meetings, work group meetings, and teacher training and coaching.